"We Ain't Dead Said the Children": A Fugitive Poetics of Life After Black Death. Issue 3 (2nd September 2021) - McCormack, Michael Brandon
ABSTRACT: This article considers how Black culture workers engage in ongoing struggles over the meaning and value ascribed to Black lives in an anti-Black world that demands Black death. The artists explored in this article deploy modes of poetics that create possibilities for fugitivity, or escape, from the overdetermination of Black life as always, already, and only "dead." Such fugitive poetics demonstrate the ways that blackness defies and exceeds social death, even as it is, perhaps, permanently tethered to the potential for premature Black death in an anti-Black world. The article also calls attention to how this poetics of fugitivity draws upon the cultural resources of religious language, beliefs, rituals, and practices to imagine and enact other worlds of possibility for Black futurity beyond the overdetermination of social and/or physical death.